CTHRC1: A New Candidate Biomarker for Improved Rheumatoid Arthritis Diagnosis - Myngbay, Askhat; Bexeitov, Yergali; Adilbayeva, Altynai; Assylbekov, Zhenisbek; Yevstratenko, Bogdan P.; Aitzhanova, Rysgul M.; Matkarimov, Bakhyt; Adarichev, Vyacheslav A.; Kunz, Jeannette (Frontiers in Immunology, 2019)
ABSTRACT Background. The purpose of this study was to determine whether plasma levels of the collagen triple helix repeat containing 1 (CTHRC1) protein can serve as a blood-based biomarker for improved diagnosis of rheumatoid arthritis (RA) patients and monitoring of RA disease activity. Methods. We measured levels of CTHRC1 in the plasma of patients diagnosed with RA, osteoarthritis (OA), reactive arthritis (ReA), as well as in healthy individuals. We then assessed the correlation between CTHRC1 protein and a range of indices including the 28-joint disease activity score (DAS28), rheumatoid factor (RF), C-reactive protein (CRP), anti–citrullinated protein antibodies (ACPA), erythrocyte sedimentation rate (ESR), as well as a panel of cytokines, including interleukin 1 beta (IL 1β), interleukin 6 (IL 6), interleukin 8 (IL 8), and interferon gamma (IFNγ). Receiver operating characteristic (ROC) analysis was further performed to assess the diagnostic value of CTHRC1. Results. CTHRC1 plasma levels were significantly elevated in RA patients compared to healthy individuals, OA and ReA patients. ROC curve and risk score analysis suggested that plasma CTHRC1 can accurately discriminate patients with RA from healthy controls and may have practical value for RA diagnosis. CTHRC1 levels were positively associated with RF, ACPA, CRP, and disease activity based on the combined index of DAS28 with CRP (DAS28-CRP), and also strongly correlated with IL-1β, IL-6, IL-8, and IFNγ. Conclusion. Our studies show that CTHRC1 is a sensitive and easy-to-measure plasma marker that differentiates between RA and healthy status and also distinguishes between RA and other forms of arthritis, such as OA and ReA. At the current level of understanding, plasma CTHRC1 levels may improve the diagnosis of RA and these findings warrant confirmation in a larger, more comprehensive patient population. Key words: Rheumatoid arthritis, biomarker, Collagen triple helix repeat containing 1, (CTHRC1), rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA), disease activity score DAS28